"Whether you like my skin or not, I am here": skilled racial minority migrant women's experiences of navigating career challenges in the White Icelandic labor market. Issue 4 (1st November 2022) - Christiansen, Thora H.; Kristjánsdóttir, Erla Sólveig
Abstract : Purpose: This study aims to explore the lived experiences of skilled racial minority migrant (SRMM) women who hold management positions in the White Icelandic labor market and to understand how gender, race, ethnicity and migrant status intersect to shape experiences of privilege and disadvantage. Design/methodology/approach: In this paper phenomenological methodology was applied to analyze in-depth interviews with twelve SRMM women. Iceland provides rich context of high gender and social equality, but limited recognition of ethnic and racial differences. Findings: SRMM women's self-efficacy and agency allowed them to source strength from their background and experiences of challenges. Through reframing they adopted a mindset of resilience and determination, proactively redefined the context, turned negatively stereotyped identities into positive assets and engaged strategically with barriers based on gender, language or migrant status. In contrast, the subtle and covert nature of racial prejudice in the context of the invisible norm of Whiteness felt impossible to address. Originality/value: The study provides insight into the experiences of SRMM women who have attained upper- and middle-management positions. The findings illuminate the overt and covert barriers that the women experience on their career journey in the context of a White labor market that emphasizes egalitarianism and gender equality but does not engage with ethnic or racial prejudice. They highlight the role of self-efficacy and agency in deploying strategies to negotiate intersecting barriers and how that agency is disadvantaged by the invisible norm of Whiteness.